2018
DOI: 10.1007/s00701-018-3607-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and morphometry of caroticoclinoid foramina in Greek dry human skulls

Abstract: The results of the present study augment the current knowledge on the morphology of key anatomical landmarks, CCF, and CCL ossification in the sellar area, indicating population differences. A significant side asymmetry in caroticoclinoid osseous bridging and foramina is highlighted. These findings are necessary for a safe surgical access to the clinoidal area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This finding likely reflects the nature of the posterior petroclinoid ligament, which is in fact a fold of dura mater (rather than a true ligament) that arises from the fixed portions of the tentorial incisura, and calcification of the dura is generally rarely seen in children [ 18 , 19 , 70 ]. There was no significant difference in the rate of ligamentous mineralisation amongst the largest ethnic groups included within the study; however, variance exists in the literature with higher rates of observed mineralisation in some (particularly Greek) populations, suggesting a potential genetic predisposition [ 14 , 30 , 57 ].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This finding likely reflects the nature of the posterior petroclinoid ligament, which is in fact a fold of dura mater (rather than a true ligament) that arises from the fixed portions of the tentorial incisura, and calcification of the dura is generally rarely seen in children [ 18 , 19 , 70 ]. There was no significant difference in the rate of ligamentous mineralisation amongst the largest ethnic groups included within the study; however, variance exists in the literature with higher rates of observed mineralisation in some (particularly Greek) populations, suggesting a potential genetic predisposition [ 14 , 30 , 57 ].…”
Section: Discussionmentioning
confidence: 90%
“…Mineralised of these ‘sellar bridges’ was relatively commonly encountered within the studied population (22.1% and 17.5%, respectively). Whilst the incidence of caroticoclinoid mineralisation reflects the majority of prior studies (12–35.67% [ 2 , 3 , 5 , 6 , 8 , 12 , 26 29 , 31 37 ]), there were some outliers [ 14 , 30 ]. The incidence of interclinoid ligamentous mineralisation was higher in the current study than in many prior studies (4–11.8% [ 2 , 12 , 26 , 27 , 29 , 36 , 37 , 39 ]), which may be secondary to the relatively long and exposed nature of the interclinoid ligament that could make it vulnerable to loss during the preparation of dry skulls.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The total CcB frequency, including complete and incomplete forms, has been reported to vary in different population groups and countries: India—12.00% [ 7 ], 16.4% [ 9 ] and 22.2% [ 10 ]; South Korea—15.7% [ 11 ]; Japan—16.6% [ 12 ]; Bosnia and Herzegovina—16.8% [ 13 ]; UK—17.5% including mixed type 2.5% [ 14 ]; Nepal—20% [ 15 ]; Turkey—34.2% [ 16 ], 35.3% [ 17 ] and 35.7% [ 18 ]; USA—34.8% [ 5 ]; and Greece—60.16% [ 19 ] and 74% [ 20 ]. Our results show that the total CcB frequency in contemporary Bulgarians is 14.3% (11.5% in males and 17.1% in females), i.e., the CcB in Bulgarians is observed more infrequently than in most of the studied populations.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the presence of these bone rings implies a medial fixation of the ACP, complicating anterior clinoidectomy and increasing the risk of injury to adjacent structures (Prathiba et al; JaiSankar et al; Skandalakis et al; Touska et al). As for ICA pathologies, the presence of CF impairs mobilization of the cavernous segment and can compress it, possessing considerable clinical significance (Efthymiou et al, 2018;Prathiba et al). In addition, there is a necessity for other maneuvers to access aneurysms in the ICA when the CF and IF are present, which increases the risk of a vascular rupture.…”
Section: Discussionmentioning
confidence: 99%